2011
DOI: 10.1186/gb-2011-12-2-r12
|View full text |Cite
|
Sign up to set email alerts
|

The role of codon selection in regulation of translation efficiency deduced from synthetic libraries

Abstract: BackgroundTranslation efficiency is affected by a diversity of parameters, including secondary structure of the transcript and its codon usage. Here we examine the effects of codon usage on translation efficiency by re-analysis of previously constructed synthetic expression libraries in Escherichia coli.ResultsWe define the region in a gene that takes the longest time to translate as the bottleneck. We found that localization of the bottleneck at the beginning of a transcript promoted a high level of expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 23 publications
(44 reference statements)
1
41
1
2
Order By: Relevance
“…The balance between supply and demand, i.e., the extent of adaptation of the tRNA pool to the codon usage in the transcriptome, could affect production levels of proteins (Qian et al, 2012). In addition, cellular fitness could be affected by the extent of a global codon-to-tRNA adaptation (Kudla et al, 2009;Navon and Pilpel, 2011), and especially highly expressed genes appear to be codon optimized (Gingold et al, 2012). It was suggested that low compatibility between demand and supply, especially if presented by highly expressed genes, can result in a global inefficient allocation of resources such as ribosomes and thus could be fitness reducing (Kudla et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The balance between supply and demand, i.e., the extent of adaptation of the tRNA pool to the codon usage in the transcriptome, could affect production levels of proteins (Qian et al, 2012). In addition, cellular fitness could be affected by the extent of a global codon-to-tRNA adaptation (Kudla et al, 2009;Navon and Pilpel, 2011), and especially highly expressed genes appear to be codon optimized (Gingold et al, 2012). It was suggested that low compatibility between demand and supply, especially if presented by highly expressed genes, can result in a global inefficient allocation of resources such as ribosomes and thus could be fitness reducing (Kudla et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo rate and accuracy of translation are affected by the use or disuse of “major” codons in Escherichia coli (Tuller et al 2010; Navon and Pilpel 2011), and early observations of genome-wide synonymous codon usage in D. melanogaster and C. elegans showed a bias toward a subset of codons (Shields et al 1988; Stenico et al 1994). This set of preferred codons corresponds to the most abundant tRNAs in the cell and, by proxy, the number of tRNA gene copies in the genome (Moriyama and Powell 1997; Duret 2000).…”
mentioning
confidence: 99%
“…Evolutionary traits may have been developed in order to optimally couple the transcription of protein-coding genes and the translation initiation of mRNA in prokaryotes. A ramp of hydrogen bonding can be one such trait that optimizes transcription efficiency at the 5 -end of CDSs so that transcription can be efficiently coupled with a ramp of translation efficiency found also at the 5 -end of CDSs 11,35,36 . Although both transcription and translation seem to be mediated by an initial ramp, the ramps have opposite efficiency.…”
Section: Discussionmentioning
confidence: 99%